Incidence of dural sac puncture during neuraxial anesthesia in cats: an observational, retrospective study. Issue 4 (April 2022) - Rondelli, Vincenzo; Otero, Pablo E; Romano, Francesca; Verdier, Natali; Bettschart-Wolfensberger, Regula; Portela, Diego A
Objectives: The aim of this study was to determine the occurrence of dural puncture, indicated by cerebrospinal fluid (CSF) outflow, in cats receiving neuraxial anesthesia through a lumbosacral injection guided by a pop sensation method. Methods: This was an observational, retrospective study. Cats that were scheduled for lumbosacral neuraxial anesthesia were included. Medical records were analyzed to investigate: (1) demographic data; (2) neuraxial anesthesia performed (epidural/spinal); (3) type of needle used, including gauge and length; (4) presence of CSF (yes/no) and/or blood (yes/no) in the hub of the needle; and (5) flicking of the tail during needle advancement (yes/no). Results: A total of 94 medical records were analyzed. A 22 G 50 mm Tuohy needle was used in all cats scheduled for an epidural injection (n = 60), whereas a 22 G 40 mm Quincke needle was used in all cats scheduled for an intrathecal injection (n = 34). CSF outflow was detected in 55/60 (91.7%) cats in which a Tuohy needle was used, and 34/34 (100%) of the cats in which a Quincke needle was used ( P  = 0.15). Flicking of the tail was detected in 41/60 (68.3%) and in 24/34 (70.6%) injections with Tuohy and Quincke needles, respectively ( P >0.99). Traces of blood, but not active blood outflow, were detected via staining of the first drops of CSF in 2/34 cats in which Quincke needles were used and in none of the cats in which Tuohy needles were used ( P  = 0.12). Conclusions and relevance: This study shows that the lumbosacral approach for neuraxial anesthesia in cats may result in a dural sac puncture when 22 G Quincke or Tuohy needles are used. The pop sensation method should be deemed effective in predicting intrathecal but not epidural needle placement.